2020
DOI: 10.3390/genes11080947
|View full text |Cite
|
Sign up to set email alerts
|

Combined PTPN11 and MYBPC3 Gene Mutations in an Adult Patient with Noonan Syndrome and Hypertrophic Cardiomyopathy

Abstract: In this report, an atypical case of Noonan syndrome (NS) associated with sarcomeric hypertrophic cardiomyopathy (HCM) in a 33-year-old patient was described. Genetic testing revealed two different disease-causing mutations: a mutation in the PTPN11 gene, explaining NS, and a mutation in the MYBPC3 gene, known to be associated with HCM. This case exemplifies the challenge in achieving a definite etiological diagnosis in patients with HCM and the need to exclude other diseases mimicking this condition (genocopie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Hypertrophic cardiomyopathy (HCM) is a heart muscle disease characterized by left ventricular hypertrophy that is not solely explained by abnormal loading conditions (i.e., hypertension, valvular heart disease, congenital heart disease) [40,41]. In nearly half of cases, the disease is inherited as an autosomal dominant genetic trait caused by mutations in genes encoding sarcomeric proteins [42][43][44][45][46] and is characterized by an extremely interindividual variability in the phenotypic expression.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…Hypertrophic cardiomyopathy (HCM) is a heart muscle disease characterized by left ventricular hypertrophy that is not solely explained by abnormal loading conditions (i.e., hypertension, valvular heart disease, congenital heart disease) [40,41]. In nearly half of cases, the disease is inherited as an autosomal dominant genetic trait caused by mutations in genes encoding sarcomeric proteins [42][43][44][45][46] and is characterized by an extremely interindividual variability in the phenotypic expression.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…This confirms the wide genetic variability observed in NS patients. A compound heterozygous mutation of MYBPC3 and PTPN11 was reported in a patient with NS and HCMP ( 31 ). Although a relationship between genotype and phenotype has been established, no study has revealed a definite mechanism ( 32 , 33 , 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The initial evaluation of a patient affected by HCM should include systematic research for clinical clues or “red flags,” obtained by pedigree analysis, clinical examination, ECG, imaging, and biochemical tests. In particular, the diagnosis of RASopathy may be suggested by facial dysmorphism, lentigines, sensorineural deafness, pulmonary stenosis, or biventricular hypertrophy ( 3 , 53 ).…”
Section: Malformation Syndromes: Rasopathiesmentioning
confidence: 99%